School Grammar in the Early Chilean Educational System: Field, Agents, and Control (1846-1865) - Savio, Karina (2025)
From a glottopolitical approach, this article analyzes, based on Bibliografía doctoral de la Universidad de Buenos Aires y catálogo cronológico de las tesis en su primer centenario 1821-1920 of Candioti, the ordinances that were sanctioned on the thesis during the first hundred years of the founding of the University of Buenos Aires in Argentina and, following the author's words, the imagery associated with the production of this genre at the beginning of the 20th century. The study shows that, in the first years, regulation focused on the topic and that, in the last ones, in which appears a concern for the formulation of scientific research and the style, new variables are added aimed at homogenizing the presentations.